Soft Tissue Implants: Additive Manufacturing of Multi‐Scale Porous Soft Tissue Implants That Encourage Vascularization and Tissue Ingrowth (Adv. Healthcare Mater. 14/2021). Issue 14 (21st July 2021) - Coulter, Fergal B.; Levey, Ruth E.; Robinson, Scott T.; Dolan, Eimear B.; Deotti, Stefano; Monaghan, Michael; Dockery, Peter; Coulter, Brian S.; Burke, Liam P.; Lowery, Aoife J.; Beatty, Rachel; Paetzold, Ryan; et al.
Abstract : In article number 2100229 by Eoin O'Cearbhaill, Garry Duffy and co‐workers, the "liquid rope coil effect" is harnessed to produce porous silicone coatings that are additively manufactured onto the surface of soft‐tissue implants, aiming to address notorious challenges of long‐term tissue integration and fibrosis associated with these implants. In vivo studies show that this coating encourages highly vascularised tissue ingrowth